Characteristics of pediatric burns complications in the main referral hospital of Mozambique - Luísa Huo; Shannon Richardson; Celma Issufo; Valeria Chicamba; Baltazar Chilundo; Natércia Fernandes; Vanda Amado (Burns Open)
Background: Burns remains a major preventable cause of injury in children worldwide with morbidity and mortality disproportionately affecting low- and middle-income countries. Complications following burn injuries in children are not well studied in Mozambique. Methods: Children between 1 month and 14 years old hospitalized for burns between 2015 and 2017 at Hospital Central de Maputo were identified retrospectively. Child and burns characteristics were compiled with complications including wound infection, sepsis, anemia, hypoalbuminemia, hyperglycemia, and dehydration. The association of complications with demographic variables and burn characteristics were assessed through bivariate analysis. Results: Of the 206 children, the most common cause of burns was hot liquids (66%), followed by fire (28%) and electrical current (6%). Children aged one to four years old were most frequently affected (54%). Of the 91 children with complications, 68% had severe burns with a significant relationship between lesion depth and complications. Among the complications, hypoalbuminemia (56%), hyperglycemia (51%), and wound infections (17%) were the most common. Children who had flame/fire burns and 2nd and 3rd degree burns were associate with a greater risk of having complications. Conclusions: Pediatric burns in the early years are more frequent in Mozambique and hold a high burden of complications. Moreover, flame/fire burns and 2nd and 3rd degree burns were associated with increased odds of complications. Primary prevention measures within the family will be critical to minimize pediatric burns and additional research is warranted to better understand clinical interventions to prevent mortality and complications in low- and middle-income countries.